Polarization Properties of Twisted Photonic Crystal Fibers - Banzer, P. (International Conference on Metamaterials, Photonic Crystals and Plasmonics, 2022)
Polarization-maintaining fibers play a pivotal role in many applications, from endoscopy and fiber-based imaging to long-distance communication. Here, we discuss the polarization properties and capabilities of a special type of chiral fibers, i.e., twisted photonic crystal fibers, which were introduced only recently and show a strong circular birefringence. Experiments confirm that they are well suited for protecting polarization sub-spaces, a very useful property both from a practical and an applied perspective.
CRIS-Team Scopus Importer:2024-12-16